The Influence of Taxpayer Awareness and Tax Sanctions on Motor Vehicle Taxpayer Compliance at the Gowa Samsat Office - Hasriyanti (Generasi Sains Indonesia, 2024)
This paper will discuss the impact of taxpayer awareness and tax sanctions on motor vehicles taxpayer compliance at the Gowa Samsat Office. Quantitative research method was used, and the sample was composed of 2,650 taxpayers enrolled at the office. A sample of 96 taxpayers was found using simple random sampling method. Questionnaires were used to measure the variables under investigation in the primary data collection. The outcomes suggest that the level of taxpayer awareness has a positive and significant impact on motor vehicle taxpayer compliance as the t-value is 5.260, which is greater than the critical t-value of 1.985 and the significance level of 0.000 < 0.041. Likewise, tax sanctions are also positively and significantly influenced on compliance as t-value of 2.076 > 1.985 and the level of significance of 0.000 < 0.041. These results imply that taxpayer education coupled with tax sanctions are effective measures towards making motor vehicle taxpayers more compliant.